Patients' and Physicians' Knowledge of Radiation Exposure Related to Spine Surgery. Issue 22 (15th November 2020) - Scott, Michelle C.; Galivanche, Anoop R.; Mets, Elbert J.; Pathak, Neil; Kahan, Joseph B.; Burroughs, Patrick J.; Varthi, Arya G.; Rubin, Lee E.; Grauer, Jonathan N.
Abstract : Study Design: Cross-sectional survey. Objective: Examine patients' and physicians' estimates of radiation exposure related to spine surgery. Summary of Background Data: Patients are commonly exposed to radiation when undergoing spine surgery. Previous studies suggest that patients and physicians have limited knowledge about radiation exposure in the outpatient setting. This has not been assessed for intraoperative imaging. Methods: A questionnaire was developed to assess awareness/knowledge of radiation exposure in outpatient and intraoperative spine care settings. Patients and surgeons estimated chest radiograph (CXR) equivalent radiation from: cervical and lumbar radiographs (anterior-posterior [AP] and lateral), computed tomography (CT), magnetic resonance imaging (MRI), intraoperative fluoroscopy, and intraoperative CT (O-arm). Results were compared to literature-reported radiation doses. Results: Overall, 100 patients and 26 providers completed the survey. Only 31% of patients were informed about outpatient radiation exposure, and only 23% of those who had undergone spine surgery had been informed about intraoperative radiation exposure. For lumbar radiographs, patients and surgeons underestimated CXR-equivalent radiation exposures: AP by five-fold ( P  < 0.0001) and seven-fold ( P  < 0.0001), respectively, and lateral by three-fold ( P  < 0.0001) and four-fold ( P  = 0.0002), respectively. For cervical CT imaging, patients and surgeons underestimated radiation exposure by 18-fold ( P  < 0.0001) and two-fold ( P  = 0.0339), respectively. For lumbar CT imaging, patients and surgeons underestimated radiation exposure by 31-fold ( P  < 0.0001) and three-fold ( P  = 0.0001), respectively. For intraoperative specific cervical and lumbar imaging, patients underestimated radiation exposure for O-arm by 11-fold ( P  < 0.0001) and 22-fold ( P  = 0.0002), respectively. Surgeons underestimated radiation exposure of lumbar O-arm by three-fold ( P  = 0.0227). Conclusion: This study evaluated patient and physician knowledge of radiation exposure related to spine procedures. Underestimation of radiation exposure in the outpatient setting was consistent with prior study findings. The significant underestimation of intraoperative cross-sectional imaging (O-arm) is notable and needs attention in the era of increased use of such technology for imaging, navigation, and robotic spine surgery. Level of Evidence: 4 Abstract : Supplemental Digital Content is available in the textA questionnaire was developed to assess patient and provider understanding of radiation exposure related to spine surgery. Patients and providers underestimated the amount of intraoperative radiation exposure associated with intraoperative cross-sectional imaging (O-arm), which is notable in the era of increased use of such technology for imaging, navigation, and robotics.